An investigation of three-dimensional scanning of human body surfaces and its use in the design and manufacture of prostheses - Richard Bibb; P. Freeman; R. Brown; Adrian Sugar; Peter L. Evans; Alan Bocca (2000)
The capture of highly accurate data describing the complex surfaces of the human body may prove extremely useful in many medical situations. The data provide a method of measuring and recording changes to the surface of a patient's soft tissue. The data may be applied to computer-controlled manufacturing techniques, such as rapid prototyping (RP). This enables accurate physical replicas of the patient topography to be produced. Such models may be used as an aid in the design and manufacture of prostheses. This paper describes an investigation aimed at identifying problems that may be encountered when scanning patients and describes the application of the resulting data in the design and manufacture of facial prostheses. The results of the experiment are presented together with a discussion of the accuracy and potential advantages afforded by this approach.